Beban Kerja Mental Perawat Dengan Metode Rating Scale Mental Effort (RSME) - Michael, Michael; Girsang, Ermi; Chiuman, Linda; Adrian, Adrian (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2022)
The nurse is a profession that determines the success of the hospital in the health service in the community due to the nurse role face the problem of the health of the patient continuously for 24 hours. High workload is a problem that often occurs in the workplace. Mental workload is the difference between the work load with the maximum capacity of the mental load of a person. This study aims to analyze the relationship multicarakteristik nurse with mental workload nurse General Hospital Royal Prima 2020 with the method of Rating Scale Mental Effort (RSME). This research type is quantitative analytic observational with the approach of cross-sectional studies and MANOVA. Data collection tool was a questionnaire. The sample in this study as many as 100 people. The results of the chi-square test showed no significant relationship between age of the nurses (p=0.001), gender of the nurse (p=0,025), the nutritional status of nurses (p=0,041), work station nurse (p=0.010), post work nurses (p=0.000), shift work nurses (p=0.000), the work of nurses (p=0.000) to the value of the mental workload of the nurse General Hospital Royal Prima 2020. The results of the multivariate test showed no relationship to age the nurse (Sig.0,010), nutritional status (Sig.0,030), office work (Sig.0,000), shift work (Sig.0,000), work period (Sig.0,000). No gender relationship (Sig.0,094), work station (Sig.0,053) against the mental workload of the nurse General Hospital (RSU) Royal Prima 2020. The Hospital is expected to improve the procedure of recruitment of nurses based on the characteristics and through a psychological test more stringent so as to absorb the nurses who have stress levels better. The nurse is expected to improve coping mechanism on the stressors that come that can do the heavy duty as a nurse.